2020
DOI: 10.1007/s43032-020-00351-y
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Birthweight and Ovarian and Uterine Size Prior to Menarche

Abstract: During pregnancy, supply of nutrients and exposure of the mother to environmental factors can influence fetus phenotype, possibly modifying growth of fetal tissues and organs. Few studies inconsistently reported that fetuses exposed to an insufficient energy supply, as those born small for gestational age, may have a reduced volume of uterus and ovaries. A retrospective analysis was performed on ultrasound data performed between 2012 and 2018 in 69 young premenarchal girls, 5 to 9 years of age, attending our e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The birth weight and birth height exhibited ovary and embryonic stem cell enrichments. Previous research reported that birthweight was a relation to maternal ovarian size 39,40 .…”
Section: Resultsmentioning
confidence: 97%
“…The birth weight and birth height exhibited ovary and embryonic stem cell enrichments. Previous research reported that birthweight was a relation to maternal ovarian size 39,40 .…”
Section: Resultsmentioning
confidence: 97%